What are urban mangroves? - Gabriela Reyes; Ashley Smyth; Laura Reynolds (EDIS)
Urban mangroves are mangroves located in cities and residential areas. While urban mangroves may be highly impacted by humans, they continue to provide important ecosystem services, or benefits to society. In fact, due to their location, more people may benefit from these urban mangroves than from pristine mangroves, which are often located in protected areas. The following document describes the role of mangroves in urban areas. This document is intended for coastal residents, coastal resource managers, and urban planners who are interested in learning about mangroves and their importance in cities. Written by Gabriela Reyes, Ashley Smyth, and Laura Reynolds, and published by the UF/IFAS Department of Soil and Water Sciences; 4 pp. https://edis.ifas.ufl.edu/ss706